(3JQJjH eG CNJUQ ef cJH GdMceGA HGdfLhes - (3YeQ GdaQNGf , YeQ Hf GdaQNGf GdWHQj, CHh MaU,J (B200 (3g` s
(3ChdgG (B:s
(3JQJjH eG ENJUQg YeQ Hf GdaQNGf GdWHQi , QMeg Gddg , ef cJH GdMceGA HGdfLhe ai CfhGY GdeSGFd hGdbVGjG Ydi GdOdGFd , hLYdgG CUhdkG jbGS YdjgG ai LejY GdeSGFd cdgG HMhd Gddg s
(3BNQgG (B:s
(3dCfgG HdG eMGdI ZjQ fGaYg ai CUhd GdUfGYI , heG CHYO gPG Yf cJGH GdCQHY hcJGH GdfeQI adjcf gPG BNQg , EP cd TF dGHO dg ef BNQ , hgPG ehVY JMeO ajg GdYGbHI ced GdJQJjH HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3HChdgG Jedc CMeO Hf CMeO Hf JeQJGT GdMfai SfI (B904 (3g`s
(3HgG fXGe GdJYbjHIs
(3HChdgG agQS ddCHhGHs
(3HChdgG HYV GdCTcGd hGdQShe s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3Gdadcs